Design and Control of Coupled Inductor DC–DC Converters for MVDC Ship Power Systems - Flavio Balsamo; Davide Lauria; Fabio Mottola (Energies, 2019)
This paper deals with the design and control aspects of modern ship power systems within the paradigm of an all-electric ship. The widespread use of power electronic converters is central in this context due to the technological advances in automation systems and the integration of the electrical propulsion systems and other components, such as electrical energy storage systems and renewable energy sources. The issue to address in this scenario is related to the request of increased performances in dynamic operation while pursuing advantages in terms of energy savings and overall system security. In addition, the presence of large load changes requires providing robustness of the control in terms of system stability. This paper is focused on medium voltage direct current (MVDC) ship power systems and the design and control of coupled inductor DC⁻DC converters. The load is handled in terms of a constant power model, which generally is considered the most critical case for testing the stability of the system. The robustness of the design procedure, which is verified numerically against large and rapid load variations, allowed us to confirm the feasibility and the attractiveness of the design and the control proposal.